Nonoperative management for invasive breast cancer after neoadjuvant systemic therapy: conceptual basis and fundamental international feasibility clinical trials - Kuerer, Henry; Heil, Jörg (Annals of surgical oncology, 2017)
With current advances in neoadjuvant systemic therapy (NST) and improved breast imaging, the potential of nonoperative therapy for invasive breast cancer has emerged as a viable option when utilizing meticulous image-guided percutaneous biopsy to document pathologic complete response. Feasibility clinical trials utilizing this approach are being performed by teams of investigators from single and multicenter/cooperative groups around the world. Imaging alone after NST lacks sufficient sensitivity and specificity in predicting pCR and therefore cannot be utilized for clinical selection of patients for omission of surgery. Imaging with adequate sampling after NST of the residual lesions (or around the remaining clip if a complete radiologic response occurs) appears to be essential in selecting patients with pCR to lower the false-negative rates based on initial reported feasibility studies to identify pCR without surgery that range from 5 to 49%. In this manuscript, recently completed, ongoing, and planned clinical feasibility trials and a new omission of surgery trial are described. Drastic rethinking of all diagnostic and therapeutic management strategies that are ordinarily utilized for patients who receive standard breast cancer surgery is required. A roadmap of essential questions and issues that will have to be resolved as the field of nonoperative breast cancer management advances is described in detail.
Gesehen am 26.11.2018